2009
DOI: 10.1039/b913962a
|View full text |Cite
|
Sign up to set email alerts
|

Acid-mediated formation of trifluoromethyl sulfonates from sulfonic acids and a hypervalent iodine trifluoromethylating agent

Abstract: A variety of sulfonic acids have been trifluoromethylated using 1-trifluoromethyl-1,2-benziodoxol-3(1H)-one under mild conditions in good to excellent yields. Initial mechanistic investigations of this reaction show a clean second-order kinetics and only very weak substrate electronic effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
51
0
9

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 97 publications
(64 citation statements)
references
References 14 publications
4
51
0
9
Order By: Relevance
“…The Brønsted acid activation of 7 was further used by Togni for the trifluoromethylation of sulfonic acids (eqn 14). 41 Strong acids were required and the use of the toluenesulfonate 60 salts failed to give the product. Interestingly, the Hammett plot showed that the substituent on the sulfonic acid had only a minor effect on the reaction rate.…”
Section: Trifluoromethylationmentioning
confidence: 99%
“…The Brønsted acid activation of 7 was further used by Togni for the trifluoromethylation of sulfonic acids (eqn 14). 41 Strong acids were required and the use of the toluenesulfonate 60 salts failed to give the product. Interestingly, the Hammett plot showed that the substituent on the sulfonic acid had only a minor effect on the reaction rate.…”
Section: Trifluoromethylationmentioning
confidence: 99%
“…This is in line with our previous observations concerning the trifluoromethylation of THF [15] and toluenesulfonic acid. [11] On the basis of these rate studies and our previous experience with these systems, we propose the mechanism shown in Scheme 3. The protonated form of reagent 1 is the reactive species.…”
mentioning
confidence: 98%
“…Despite their purported soft nature, reagents 1 and 2 do trifluoromethylate alcohols and sulfonic acids upon activation with Lewis [10] and Brønsted acids, [11] respectively, thus significantly expanding their application range.…”
mentioning
confidence: 99%
“…Entgegen ihrer vermeintlich weichen Natur trifluormethylieren 1 und 2 Alkohole oder Sulfonsäu-ren nach Aktivierung mit Lewis- [10] bzw. Brønsted-Säuren, [11] womit ihr Einsatzbereich erheblich erweitert wird.…”
unclassified